Mutations in the K-ras oncogene induced by 1,2-dimethylhydrazine in preneoplastic and neoplastic rat colonic mucosa. - Jacoby, R F (1991)
These experiments were conducted to determine whether point mutations activating K-ras or H-ras oncogenes, induced by the procarcinogen 1,2-dimethylhydrazine (DMH), were detectable in preneoplastic or neoplastic rat colonic mucosa. Rats were injected weekly with diluent or DMH at 20 mg/kg body wt for 5, 10, 15, or 25 wk, killed, and their colons dissected. DNA was extracted from diluent-injected control animals, histologically normal colonic mucosa from carcinogen-treated animals, and from carcinomas. Ras mutations were characterized by differential hybridization using allele-specific oligonucleotide probes to polymerase chain reaction--amplified DNA, and confirmed by DNA sequencing. While no H-ras mutations were detectable in any group, K-ras (G to A) mutations were found in 66% of DMH-induced colon carcinomas. These mutations were at the second nucleotide of codons 12 or 13 or the first nucleotide of codon 59 of the K-ras gene. The same type of K-ras mutations were observed in premalignant colonic mucosa from 2 out of 11 rats as early as 15 wk after beginning carcinogen injections when no dysplasia, adenomas, or carcinomas were histologically evident, suggesting that ras mutation may be an early event in colon carcinogenesis.